2018
DOI: 10.1186/s40851-017-0086-3
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient generation of knock-in transgenic medaka by CRISPR/Cas9-mediated genome engineering

Abstract: BackgroundMedaka (Oryzias latipes) is a popular animal model used in vertebrate genetic analysis. Recently, an efficient (~ 30%) knock-in system via non-homologous end joining (NHEJ) was established in zebrafish using the CRISPR/Cas9 system. If the same technique were applicable in medaka, it would greatly expand the usefulness of this model organism. The question of the applicability of CRISPR/Cas9 in medaka, however, has yet to be addressed.ResultsWe report the highly efficient generation of knock-in transge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 21 publications
1
40
0
Order By: Relevance
“…Using genetically engineered fish, we will be able to investigate the pleiotropic effects of candidate genes. Finally, gene replacement has been successfully conducted in several fish species (Kimura et al, 2014;Watakabe et al, 2018), which may be possible in sticklebacks in the near future.…”
Section: The Future Of Physiological Genomics Of Seasonal Reproductiomentioning
confidence: 99%
“…Using genetically engineered fish, we will be able to investigate the pleiotropic effects of candidate genes. Finally, gene replacement has been successfully conducted in several fish species (Kimura et al, 2014;Watakabe et al, 2018), which may be possible in sticklebacks in the near future.…”
Section: The Future Of Physiological Genomics Of Seasonal Reproductiomentioning
confidence: 99%
“…Single cell transcriptome sequencing can, for example, be used to study the evolution of gene regulatory networks underlying sex determination. All of these technologies can help to identify candidate loci that may contribute to evolutionary processes of interest, while the phenotypic effects of natural genetic variation at these loci can now be assessed using gene-editing tools (Gutierrez-Triana et al, 2018; Letelier et al, 2018; Murakami et al, 2017; Watakabe et al, 2018). Together these technological advances have set the stage for scientists to begin converting the described natural diversity of ricefishes into a better understanding of the molecular basis of evolutionary processes.…”
Section: New Opportunities From Technological Advancesmentioning
confidence: 99%
“…More recently, the gene-editing tool CRISPR/Cas9 was also established in medaka and employed in multiple studies (e.g. Gutierrez-Triana et al, 2018; Letelier et al, 2018; Murakami et al, 2017; Watakabe et al, 2018). In many fields, including cancer research, medaka serves as complementary model to the well-established zebrafish (Schartl and Walter, 2016; Takeda and Shimada, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…CRISPR/Cas9 has been explored as a knock-in system in model fishes targeting reporter/driver genes in medaka 30,31 and zebrafish 32,33 . But limited studies for CRISPR/Cas9 knock-in were found on farmed fish 7,34 , and these studies primarily focused on non-performance genes.…”
mentioning
confidence: 99%